2010
DOI: 10.1002/bmc.1417
|View full text |Cite
|
Sign up to set email alerts
|

Applications of capillary electrophoresis with capacitively coupled contactless conductivity detection (CE‐C4D) in pharmaceutical and biological analysis

Abstract: Conductivity detection, which is universal in capillary electrophoresis (CE), has received considerable attention, since the introduction of the axial capacitively coupled contactless detector C(4)D in 1998. This detector is made of two electrodes which are placed cylindrically around the CE capillary and connected to the AC oscillator. The distance between the electrodes is the detection gap. In this review, applications of CE and MCE with C(4)D in pharmaceutical and biological analysis are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 75 publications
0
37
0
Order By: Relevance
“…The CE–C 4 D technique has been applied increasingly for the determination of many pharmaceutical and biological entities . Specifically, the CE–C 4 D method was used for the determination of many antibiotics, for example, colistin and tobramycin .…”
Section: Introductionmentioning
confidence: 99%
“…The CE–C 4 D technique has been applied increasingly for the determination of many pharmaceutical and biological entities . Specifically, the CE–C 4 D method was used for the determination of many antibiotics, for example, colistin and tobramycin .…”
Section: Introductionmentioning
confidence: 99%
“…However, CE-MS is expensive and its use is limited to separations employing volatile BGEs and thus the application field is rather narrow. On the other hand, conductivity detection in CE is very simple and has developed rapidly over the last decade, in the form of axial capacitively coupled contactless conductivity detection (C 4 D) [22][23][24][25]. C 4 D cells are readily connected to the separation capillary, the measurement is robust and sensitive, at a micromolar level, and thus the technique has become a useful complement to UV-vis photometry.…”
Section: Introductionmentioning
confidence: 99%
“…A series of applications of the method for clinical analysis of diverse biological samples have been reported [29][30][31][32][33][34][35][36][37][38][39][40]. Recent reviews on the applications of CE-C 4 D in pharmaceutical analysis [41,42] can also be found.…”
Section: Introductionmentioning
confidence: 99%